2017
DOI: 10.4103/1735-1995.199096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intrauterine injection of human chorionic gonadotropin before embryo transfer on pregnancy rate: A prospective randomized study

Abstract: Background:Human chorionic gonadotropin (hCG) as the most important factor to controlled implantation is one of the early embryonic signals in primates that is secreted by the embryo before its implantation. This study was designed to assess the effects of intrauterine injection of hCG before the embryo transfer in an in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) cycle on pregnancy rate in infertile patients.Materials and Methods:This randomized study was done on 100 infertile patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
11
1
1
Order By: Relevance
“…As shown in Fig. 2 b , all included studies 3 , 914 , 17 , 18 , 19 , 20 , 21 reported the clinical pregnancy rate, and significant heterogeneity was observed among the studies (I 2 = 73%, p < 0.0001). A random effects model analysis of the pooled data revealed a statistically significant increase in the clinical pregnancy rate in the hCG group, compared with the control group (RR = 1.33; 95% CI: 1.12 – 1.58).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…As shown in Fig. 2 b , all included studies 3 , 914 , 17 , 18 , 19 , 20 , 21 reported the clinical pregnancy rate, and significant heterogeneity was observed among the studies (I 2 = 73%, p < 0.0001). A random effects model analysis of the pooled data revealed a statistically significant increase in the clinical pregnancy rate in the hCG group, compared with the control group (RR = 1.33; 95% CI: 1.12 – 1.58).…”
Section: Resultsmentioning
confidence: 96%
“…Of the 22 articles that met the initial selection criteria, 10 were excluded after a careful reading of the full text. Finally, this meta-analysis included 12 RCTs 3 , 9 , 10 , 11 , 12 , 13 , 14 , 17 , 18 , 19 , 20 , 21 involving 3241 patients. The characteristics of each included study are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the above established an evidence base for clinical trials. A moderate number of clinical trials have been performed so far (summarized in Table 2 ), with the majority of them being randomized controlled trials ( Mansour et al, 2011 ; Hong et al, 2014 ; Santibañez et al, 2014 ; Zarei et al, 2014 ; Aaleyasin et al, 2015 ; Wirleitner et al, 2015 ; Dehghani Firouzabadi et al, 2016 ; Navali et al, 2016 ; Huang et al, 2017a ; Mostajeran et al, 2017 ; Boonsuk et al, 2018 ; Hafezi et al, 2018 ; Laokirkkiat and Thanaboonyawat, 2019 ). Despite the anticipation for solid evidence, an in-depth evaluation reveals high heterogeneity due to different methodologies applied.…”
Section: Approaches To Improve Endometrial Receptivity In Unexplainedmentioning
confidence: 99%
“…The study concluded that 500 IU of hCG in 1 mL of culture media mirrors the ideal concentration to be injected into the uterine cavity, about 7 minutes prior to ET, promising enhanced pregnancy rates (10). Hitherto, several prospective studies have advocated the benefit of hCG administration as a valid option for improvement of pregnancy rates during IVF/ICSI cycles (6,(11)(12)(13). In contrast, other studies have reported no positive effect of this approach with respect to pregnancy rates, and particularly for cases involving blastocyst ET (14,15).…”
mentioning
confidence: 99%